GLC and HPLC Studies on Residual Effects of Two Carbamates on Food Quality of Glycine max L and Its Possible Reversion by Neem - Mulchandani, Pushpa; Gupta, S.K.; Mulchandani, Vasudev (Asian Journal of Chemistry, 2012)
From the results it has been observed that two carbamates (Aldicarb and carbofuran) at all concentrations were inhibitory to the fool quality of Glycine max L. (soyabean). These carbamates were translocated and got accumulated in different parts of the plant. An analysis of residual carbamates by GLC and analysis of protein content (amino acids) by HPLC in seeds of plants after treating with graded concentrations of carbamates indicate a linear increases in the amount of toxic residue and a linear decrease in protein content in seeds. But application of an optimum concentrations of extract of neem (Azadirachta indica), i.e., 10 mg/litre along with 5 mg/litre carbamate significantly reduced the level of toxic residue and increased the number of amino acids (protein content) in seeds, thus improving the food quality of Glycine max L.